2016
DOI: 10.4196/kjpp.2016.20.2.161
|View full text |Cite
|
Sign up to set email alerts
|

CRM1 inhibitor S109 suppresses cell proliferation and induces cell cycle arrest in renal cancer cells

Abstract: Abnormal localization of tumor suppressor proteins is a common feature of renal cancer. Nuclear export of these tumor suppressor proteins is mediated by chromosome region maintenance-1 (CRM1). Here, we investigated the antitumor eff ects of a novel reversible inhibitor of CRM1 on renal cancer cells. We found that S109 inhibits the CRM1-mediated nuclear export of RanBP1 and reduces protein levels of CRM1. Furthermore, the inhibitory eff ect of S109 on CRM1 is reversible. Our data demonstrated that S109 signifi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Although this gene has been detected in both kidney tumors and non-tumorous kidney tissues, its expression in patients with metastatic disease was higher than that in those without metastasis. RAN binding protein 1 gene (Ranbp1) encodes a protein that forms a complex with Ras-related nuclear protein (Ran) and metabolizes guanoside triphosphate (GTP), this complex participates in cell cycle regulation by controlling the transport of proteins and nucleic acids into the nucleus (Liu et al, 2016). Cell growth and cell cycle regulation are important events in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although this gene has been detected in both kidney tumors and non-tumorous kidney tissues, its expression in patients with metastatic disease was higher than that in those without metastasis. RAN binding protein 1 gene (Ranbp1) encodes a protein that forms a complex with Ras-related nuclear protein (Ran) and metabolizes guanoside triphosphate (GTP), this complex participates in cell cycle regulation by controlling the transport of proteins and nucleic acids into the nucleus (Liu et al, 2016). Cell growth and cell cycle regulation are important events in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, a study was conducted that showed an increased expression of Crm1 in cancerous tissues, and the results of this study indicated a possible relationship between Crm1 and cancer (van der Watt et al, 2009). Additionally, it was shown in advanced studies that the increased expression of Crm1 was verified in 17 different tumor types, including multiple myeloma (Tai et al, 2014), ovarian cancer (Noske et al, 2008), osteosarcoma (Yao et al, 2009), esophageal cancer (van der Watt et al, 2014Yang et al, 2014), glioma , gastric cancer (Zhou et al, 2013), and renal cancer (Liu et al, 2016). This overexpression was correlated with poor patient survival and was reported to have a negative prognostic value (Turner et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…It was also reported that cell cycle inhibitors involved in the pathogenesis of cancer were targeted by Crm1; tumor suppressor proteins, including BRAC1, the FOXOs, Rb, APC, RASSF2, Merlin, nucleophosmin, survivin, STAT, a κB-α inhibitor (IκB-α), and transcription factors NFY/ CBP, Sp1, and p53, are all affected by Crm1 overexpression and contribute to cellular transformations together with Crm1. Crm1 deregulation has been demonstrated mainly in cervical squamous cell carcinoma (van der Watt et al, 2009), though also in many other cancer types, such as esophageal cancer (van der Watt et al, 2014;Yang et al, 2014), multiple myeloma (Tai et al, 2014), and renal cancer (Liu et al, 2016), and it has been shown that Crm1 inhibition has the potential to target continuously proliferating cancer cells (Kau et al, 2004). Crm1-targeting agents containing inhibitors, such as LMB (Newlands et al, 1996;Wolff et al, 1997;Kudo et al, 1999), N-azolylacrylate analogs (Daelemans et al, 2002), Valeriana fauriei and Alpinia galanga l (Tamura et al, 2009), the FOXO family (Kau et al, 2003), and the novel SINE (Sakakibara et al, 2011), are highly potent candidate molecules that could be used to develop anticancer therapies when the role of Crm1 is confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found that S109 can inhibit the CRM1-mediated nuclear export of tumor suppressor protein RanBP1 and decreases the protein levels of CRM1, which indicates that CRM1 is a therapeutic target for the treatment of renal cancer and is a novel reversible CRM1 inhibitor. S109 could be a candidate for renal cancer therapy [28].…”
Section: S109mentioning
confidence: 99%